Action research on enhancing accounting students’ oral presentation skill - Chandren, Sitraselvi; Yaacob, Aizan (2016)
The purpose of this action research is to enhance the accounting students’ oral presentation skill as this soft skill is prominent for career opportunity and success in accounting profession.This action research employed spiral reflective cycles for the 37 participants of accounting students.A total of four cycles are carried out in this action research to enrich the students’ oral presentation skill.This study used rubric assessment and video stimulation interview techniques to improve students’ oral presentation skill.The results of this action research evidenced that these students have enriched their oral presentation skill from the four reflective spiral cycles.The video stimulation interview is a significant technique to enhance students’ oral presentation skill.The oral presentation skill is an essential soft skill that contributes to produce a work ready accounting graduate.Thus, this action research contributed in producing a work ready accounting graduate by enriching their oral presentation skill.